Coupled continuum and condensation–evaporation pore network model of the cathode in polymer-electrolyte fuel cell. (23rd March 2017) - Belgacem, Najib; Prat, Marc; Pauchet, Joel
Abstract: A model of the cathode side of a Proton Exchange Membrane Fuel Cell coupling the transfers in the GDL with the phenomena taking place in the cathode catalyst layer and the protonic transport in the membrane is presented. This model combines the efficiency of pore network models to simulate the liquid water formation in the fibrous substrate of the gas diffusion layer (GDL) and the simplicity of a continuum approach in the micro-porous layer (MPL). The model allows simulating the liquid pattern inside the cathode GDL taking into account condensation and evaporation phenomena under the assumption that the water produced by the electro-chemical reactions enters the MPL in vapor form from the catalyst layer. Results show the importance of the coupling between the transfers within the various layers, especially when liquid water forms as the result of condensation in the region of the GDL fibrous substrate located below the rib. Highlights: A coupled continuum and condensation pore network model of the cathode in PEMFC is presented. Location of liquid water condensation is in good agreement with already published experiments. Current density distribution at rib-channel scale is discussed for coupled and non-coupled model.